Evaluation of associated risk factors of near miss obstetrics cases at B.P. Koirala Institute of Health Sciences, Dharan, Nepal - Khadka, Madan; Uprety, Dhruba Kumar; Rai, Rubina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In 2011, around 273,465 women died worldwide during pregnancy, childbirth or within 42 days after childbirth. Near-miss is recognized as the predictor of level of care and maternal death. The objective of the study was to evaluate the associated risk factors of near miss obstetric cases. Methods: A prospective observational study was done from August 1, 2014 to July 30, 2015 in Department of Obstetrics and Gynecology at BPKIHS hospital, tertiary care hospital in Eastern Nepal, Dharan. Case eligible by 5 factor scoring system and WHO near miss criteria were evaluated. Risk factors included severe hemorrhage, hypertensive disorders, complication of abortion, ruptured uterus, medical/surgical condition and sepsis. Results: A total of 9,727 delivery were attended during the study period from August 2014 to July 2014. There were 6307 (71.5%) vaginal delivery and 2777 (28.5%) caesarean section and 181 perinatal death with total of 9,546 livebirth. 162 near miss and 16 maternal death occurred during the study. Maternal near miss rate of 16.6 per 1000 live birth, Women with life-threatening conditions of 172, Severe maternal outcome ratio of 18.64, Maternal near-miss: mortality ratio: 10.1:1, Mortality index: 8.98%. Risk factors were obstetric hemorrhage 27.8%, abortion/ectopic 27.2%, eclampsia 16%, medical/surgical condition 14.8%, sepsis 13.6%, severe preeclamsia 11.1%, ruptured uterus 3.1%, and molar pregnancy 1.9% and cardiovascular and coagulation dysfunction as a major life-threatening condition and sepsis (25%) was the major cause of mortality. Conclusions: Haemorrhage and hypertensive disorders are the leading causes of near miss event. Evaluation of associated risk factor can be potential tool for reduction of maternal morbity and mortality.